Sperm long non-coding RNAs as markers for ram fertility - Hitit, Mustafa; Kaya, Abdullah; Memili, Erdogan (Frontiers in Veterinary Science, 2024)
It is critical for sheep farming to accurately estimate ram fertility to maintain reproductive effectiveness and production profitability. However, there is currently a lack of reliable biomarkers to estimate semen quality and ram fertility that is hindering advances in animal science and technology. The objective of this study was to uncover long non-coding RNAs (lncRNA) in sperm from rams with distinct fertility phenotypes. Mature rams were allocated into two groups: High and Low Fertility (HF; n = 31; 94.5±2.8%, LF; n = 25; 83.1±5.73%; P = 0.028) according to the pregnancy rates sired by the rams (average pregnancy rate; 89.4±7.2%). Total RNAs were isolated from sperm of the highest and lowest fertility rams (n = 4, pregnancy rate; 99.2 ±1.6%, and 73.6 ±4.4%, respectively) followed by next generation sequencing of the transcripts. We uncovered 11,209 lncRNAs from the sperm of rams with HF and LF fertility. In comparison to each other, there were 93 differentially present lncRNAs in sperm from the two distinct fertility phenotypes. Of these, 141 mRNAs were upregulated, and 134 were downregulated between HF and LF, respectively. Genes commonly enriched for 9+2 motile cilium and sperm flagellum were ABHD2, AK1, CABS1, ROPN1, SEPTIN2, SLIRP, and TEKT3. Moreover, CABS1, CCDC39, CFAP97D1, ROPN1, SLIRP, TEKT3, and TTC12 were commonly enriched in flagellated sperm motility and sperm motility. Differentially expressed (DE) mRNAs were enriched in the top 16 KEGG pathways. Targets of the differentially lncRNAs elucidate functions in cis and trans manner using genetic context of the lncRNA locus and lncRNA sequences revealed that 471 mRNAs targets of 10 lncRNAs. This study illustrates the existence of potential lncRNA biomarkers that can be implemented in analyzing the quality of ram sperm and determining the sperm fertility and used in breeding soundness exams for precision livestock farming to ensure food security on a global scale.